Distribution, use, management, regulation, and future concerns of reef-building corals based on administrative documents in Japan. (July 2022) - Abe, Hiroya; Kitano, Yuko F.; Fujita, Tomohiro; Yamano, Hiroya
Abstract: Ecosystems composed of reef-building corals play an essential role in maintaining biodiversity and as a place for tourism and fisheries. Where there is a gap between the distribution, use, management, regulation, and future concerns/interests of corals, the value of coral communities may not be properly received, and the resource may be degraded under future environmental change. We organized records of coral occurrence in each prefecture in Japan. We assessed coral use and management status based on administrative documents. Moreover, we compiled information on how laws regulate coral harvesting. Concerns for future changes were extracted from climate change adaptation plans. Text analysis of several administrative documents showed that the frequency of occurrence of coral-related keywords varied greatly among prefectures and documents. Comparing the information on coral distribution areas and the status of use, management, and regulation organized in this study for each prefecture revealed significant gaps in some prefectures, suggesting that management and regulation should be reviewed following the distribution status. With the projected increase in the magnitude of bleaching and expansion of coral distribution areas as water temperatures rise due to global warming, one of the strengths of this study is the identification of the current status and issues of the gap between distribution and use, management, and regulation. In areas where the spatial gradient of the environment/ecosystem is considerable or where significant changes in the environment/ecosystem are expected in the future, it is essential to establish a utilization and management system that reflects the characteristics of these areas.